An efficient alpha helix model and simulation framework for stationary electrostatic interaction force estimation - Guy G. Butcher (Nature Portfolio, 2021)
Abstract The alpha-helix coiled-coils within talin’s rod domain have mechanical and signalling functions through their unfolding and refolding dynamics. A better understanding of talin unfolding events and the forces that are involved should allow better prediction of talin signalling. To overcome the current limitations of force measuring in molecular dynamics simulations, a new simulation framework was developed which operated directly within the force domain. Along with a corresponding alpha-helix modelling method, the simulation framework was developed drawing on robotic kinematics to specifically target force interactions. Coordinate frames were used efficiently to compartmentalise the simulation structures and static analysis was applied to determine the propagation of forces and torques through the protein structure. The results of the electrostatic approximation using Coulomb’s law shows a simulated force interaction within the physiological relevant range of 5–40 pN for the rod sub-domains of talin. This covers the range of forces talin operates in and is 2–3 orders of magnitude closer to experimentally measured values than the compared all-atom and coarse-grained molecular dynamics. This targeted, force-based simulation is, therefore, able to produce more realistic forces values than previous simulation methods.